Psicologia e esporte: a experiência do crossfiteiro no Maranhão - PRIVADO, Thaísa Drielle Louzeiro (2022)
When considering sport as a sociocultural phenomenon capable of producing and reproducing values and behavior, it was proposed in this research to understand the relationships between sports practice and the way of being of its practitioners, choosing a sport modality of Crossfit as the object of this study. Defined as a program of strength and central conditioning, Crossfit was developed by the American Greg Glassman, in 1995 and is composed of aerobic exercises, running, weightlifting, among others. In 2018, Brazil reached the second place with the largest number of boxes affiliated to Crossfit Inc. In this scenario, the thesis Psychology and Sport: the experience of the crossfitter in Maranhão is an exploratory and descriptive research that investigates the narrative of practitioners of the sport, analyzing the phenomena found based on studies on sport and sport psychology, Crossfit, the relationships of the body and fitness culture in contemporaneity, in addition to the phenomenological perspective for analyzing the narratives. As main objective, Crossfit was analyzed as a social and sporting phenomenon, understanding how this practice is integrated into the ways of being of its practitioners, their experiences and relationships with the world. And as specific objectives, sport was contextualized as a contemporary sociocultural phenomenon; Crossfit is fulfilled as a sport modality and social phenomenon; the Crossfit practitioners from Maranhão were characterized; and presenters themselves possible impacts of the Covid-19 pandemic, for practitioners of this modality. The methodological path begins with a bibliographical survey, in the databases of Scielo and Google Academic, as well as in the official website of Crossfit.com, and the analysis of the reports collected through a semi-structured interview script. experience, based on the phenomenological method proposed by Amadeo Giorgi (1985). Among the phenomena found, Crossfit stands out as a configuration of sport and physical exercise in contemporaneity, carrying with it a diversity of constituent elements of the socioeconomic and cultural context of Western capitalism that result in obtaining in the ways of being of the people who practice it, such as search for overcoming, for an organized and dynamic routine, adaptable to the day- to-day demands, for corporal and esthetic changes even in the pandemic period. Crossfit is still designed as a space for socialization, emotional and affective release. Such phenomena found illustrate the reality in Maranhão and will certainly serve as a basis for other studies presented on the scarcity of data on the subject.